2009
DOI: 10.7326/0003-4819-150-6-200903170-00008
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin for the Prevention of Cardiovascular Disease: U.S. Preventive Services Task Force Recommendation Statement

Abstract: Encourage men age 45 to 79 years to use aspirin when the potential benefit of a reduction in myocardial infarctions outweighs the potential harm of an increase in gastrointestinal hemorrhage. (A recommendation) Encourage women age 55 to 79 years to use aspirin when the potential benefit of a reduction in ischemic strokes outweighs the potential harm of an increase in gastrointestinal hemorrhage. (A recommendation) Evidence is insufficient to assess the balance of benefits and harms of aspirin for cardiovascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
159
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 475 publications
(161 citation statements)
references
References 0 publications
0
159
1
1
Order By: Relevance
“…In a meta‐analysis, investigators observed a significant 12% relative risk reduction in nonfatal cardiovascular events achieved with aspirin use among previously healthy adults 3. These and other studies led the USPSTF in 2009 to recommend low‐dose aspirin for primary prevention in men aged 45 to 79 years and women aged 55 to 79 years7 with similar recommendations from other authoritative bodies 12, 13. Since then, additional analyses also suggest that aspirin use might be associated with a reduction in CVD mortality26 and that this benefit is likely cost‐effective 27…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a meta‐analysis, investigators observed a significant 12% relative risk reduction in nonfatal cardiovascular events achieved with aspirin use among previously healthy adults 3. These and other studies led the USPSTF in 2009 to recommend low‐dose aspirin for primary prevention in men aged 45 to 79 years and women aged 55 to 79 years7 with similar recommendations from other authoritative bodies 12, 13. Since then, additional analyses also suggest that aspirin use might be associated with a reduction in CVD mortality26 and that this benefit is likely cost‐effective 27…”
Section: Discussionmentioning
confidence: 99%
“…These bleeding risks are emphasized in the USPSTF report recommending aspirin use for primary prevention. The USPSTF report recommends aspirin use for those with increased Framingham risk scores for CVD 7. Others have recently emphasized these risks 35.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regular aspirin use led to a 24% reduction in risk for ischemic stroke in women as demonstrated in the Women's Health Study in 2005 13. These studies and others18, 19, 20 led the US Preventive Services Task Force (USPSTF) in 2009 to develop a class A recommendation for PP aspirin use in men aged 45 to 79 years and women aged 55 to 79 years for whom CVD ischemic event prevention outweighs bleeding risk 21. This recommendation provided a distinctly favorable recommendation for aspirin use compared with the 2002 statement.…”
Section: Introductionmentioning
confidence: 97%
“…In 2009, the United States Preventive Services Task Force (USPSTF) assigned grade‐A recommendations for the use of aspirin in men ages 45 to 79 years for the prevention of myocardial infarction (MI) and in women ages 55 to 79 years for the prevention of ischemic stroke, in both cases where the prevention risks outweigh the risk of gastrointestinal (GI) bleeding 2. These recommendations are echoed to varying degrees in multiple cardiovascular disease prevention guidelines, including those of the American Heart Association (AHA) 3.…”
Section: Introductionmentioning
confidence: 99%